Comparative analysis of modern approaches to the correction of hyperprolactinemia in adolescent girls with menstrual dysfunction - O. V. Gorbunova; I. O. Yurchenko (Publishing House TRILIST, 2020)
Purpose of the study: a comparative analysis of the hormonal profile in patients with menstrual disorders on the background of hyperprolactinemia during puberty after different treatments. Materials and methods. 94 adolescent girls with formation of menstrual function were examined. The mean age of patients was 14.0 ± 1.5 years. Participants were divided into groups according to the management: I (main) group - girls with menstrual disorders on the background of hyperprolactinemia during puberty, who received differentiated approach proposed by study authors (n = 33); II (comparison) group - girls with menstrual disorders on the background of hyperprolactinemia during puberty, who received conventional treatment (n = 31); III (control) group - healthy girls in puberty (n = 30). A high-calorie, balanced, protein-enhanced diet and psychotherapy for girls with severe weight loss; a high-calorie, balanced, protein-enhanced diet for girls with insufficient body weight; physical training for girls with normal weight and overweight was recommended. A comprehensive anti-stress therapy for high levels of personal and situational anxiety was recommended. The drug with a mild dopaminergic effect Cyclodynon® to correct prolactin levels and normalize menstrual function in adolescent girls was used. Results. The obtained data indicate a decrease in ovarian reserve in girls with menstrual disorders on the background of hyperprolactinemia from adolescence age. Dynamics of prolactin reduction in girls with hyper- and hypomenstrual syndromes and amenorrhea in group I was faster compared to group II as a result of treatment. Prolactin level in patients with hypermenstrual syndrome as early as 3 months after the start of therapy did not differ from its level in healthy girls; in patients with hypomenstrual syndrome and amenorrhea - after 6 months. Therapeutic effect persisted throughout the first year of observation. Conclusions. A differentiated approach to the management of patients with menstrual disorders on the background of hyperprolactinemia during puberty was found to be twice as effective as in conventional measures.